Reaction of bond markets to CEO option exercises - Swetha Balachandran (2011)
Despite the large literature about the effect of CEO option compensation on shareholder value, little is understood on how this option compensation affects bondholder welfare. In this paper, we investigate the bond price reaction toward CEO option exercises. We find a significant positive reaction of bond price when the CEO exercises their stock option. The evidence is consistent with the view that stock option exercise decreases the CEO’s risk-taking incentives and thus is a positive event for bondholders.